Transcriptional Regulation of Autophagy: Mechanisms and Diseases - Di Malta, Chiara; Cinque, Laura; Settembre, Carmine (Frontiers in Cell and Developmental Biology, 2019)
Macro(Autophagy) is a catabolic process that relies on the cooperative function of two organelles: the lysosome and the autophagosome. The recent discovery of a transcriptional gene network that co-regulates the biogenesis and function of these two organelles, and the identification of transcription factors, miRNAs and epigenetic regulators of autophagy, demonstrated that autophagy is controlled by both transcriptional and post-transcriptional mechanisms. In this review article we discuss the nuclear events controlling autophagy, focusing particularly on the role of the MiT/TFE transcription factor family. In addition, we will discuss the evidence suggesting that the transcriptional regulation of autophagy might be targeted for the treatment of human genetic diseases.